Porcine Organoid-Derived Monolayers in Static and Dynamic Platforms: Toward a Biomimetic In Vitro Intestinal Model - López Boix, Rut; Solanas , Estela (Jornada de Jóvenes Investigadores del I3A, 2025)
Porcine intestinal organoid-derived monolayers were cultured under static and dynamic conditions. The dynamic system promoted earlier barrier maturation, enhanced epithelial differentiation, and stable permeability, reflecting improved physiological relevance. These findings support organ-on-chip platforms as effective, biomimetic tools for studying post-weaning intestinal function in vitro, reducing reliance on animal models.